A new peptide inhibitor of C1QBP exhibits potent anti‐tumour activity against triple negative breast cancer by impairing mitochondrial function and suppressing homologous recombination repair - Xingxing Li; Yue Wu; Min Zhang; Fengliang Wang; Hong Yin; Yanrong Zhang; Shuli Zhao; Jiehua Ma; Mingming Lv; Cheng Lu (Clinical and Translational Medicine, 2025)
Abstract C1QBP exhibits heightened expression across a spectrum of tumours, thereby fostering their proliferation and metastasis, rendering it a pivotal therapeutic target. Nevertheless, to date, no pharmacological agents capable of directly targeting and inducing the degradation of C1QBP have been identified. In this study, we have unveiled a new peptide, PDBAG1, derived from the precursor protein GPD1, employing a peptidomics‐based drug screening strategy. PDBAG1 has demonstrated substantial efficacy in suppressing triple‐negative breast cancer (TNBC) both in vitro and in vivo. Its mechanism of action involves mitochondrial impairment and the inhibition of oxidative phosphorylation (OXPHOS), achieved through direct binding to C1QBP, thereby promoting its ubiquitin‐dependent degradation. Concomitantly, due to metabolic adaptability, we have observed an up‐regulation of glycolysis to compensate for OXPHOS inhibition. We observed an aberrant phenomenon wherein the hypoxia signalling pathway in tumour cells exhibited significant activation under normoxic conditions following PDBAG1 treatment. Through size‐exclusion chromatography (SEC) and isothermal titration calorimetry (ITC) assays, we have validated that PDBAG1 is capable of binding C1QBP with a Kd value of 334 nM. Furthermore, PDBAG1 inhibits homologous recombination repair proteins and facilitates synergism with poly‐ADP‐ribose polymerase inhibitors in cancer therapy. This underscores that PDBAG1 ultimately induces insurmountable survival stress through multiple mechanisms while concurrently engendering therapeutic vulnerabilities specific to TNBC. Key points The newly discovered peptide PDBAG1 is the first small molecule substance found to directly target and degrade C1QBP, demonstrating significant tumour inhibitory effects and therapeutic potential.